2012
DOI: 10.1093/biolreprod/87.s1.379
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Trophoblastic Cell Differentiation and Binucleation Involves Enhanced Endogenous Retrovirus Element Expression.

Abstract: Background: Endogenous retrovirus (ERV) envelope (env) genes are involved in the differentiation of trophoblastic cells in humans and mice. However, there is limited information about their roles in ruminant trophoblastic cells. Thus, we attempted to explore the possible roles of ERV elements in the binucleation of bovine trophoblastic cells using in vitro bovine trophoblastic (BT) cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…3). Interestingly, two of the families, Bos-Env4 and Bos-Env5, correspond to previously identified sequences (23,24); the other three families had not been described previously. Analysis of the overall structure of the five identified Env families (Figs.…”
Section: In Silico Search For Retroviral Env Genes Within the Cow (Bosupporting
confidence: 55%
See 1 more Smart Citation
“…3). Interestingly, two of the families, Bos-Env4 and Bos-Env5, correspond to previously identified sequences (23,24); the other three families had not been described previously. Analysis of the overall structure of the five identified Env families (Figs.…”
Section: In Silico Search For Retroviral Env Genes Within the Cow (Bosupporting
confidence: 55%
“…Both the bos-env1 orthol- (Table S2). Bos-Env4 and BosEnv5 (chr24) correspond to the Env of the previously identified bovine ERVs BERV-K1 and -K2 (23,24), respectively. BFV, bovine foamy virus; BLV, bovine leukemia virus; ENTV, enzootic tumorigenic virus; FeLV, feline leukemia virus; JSRV, Jaagsiekte retrovirus; HERV, human ERV; HFV, human foamy virus; HIV, human immunodeficiency virus; MoMLV, Moloney murine leukemia virus; mIAPE, Mus musculus intracisternal A-type particle with an envelope gene; MMTV, murine mammary tumor virus; MPMV, Mason-Pfizer monkey virus; OMVV, ovine Maedi-Visna virus; PERV, porcine ERV.…”
Section: In Silico Search For Retroviral Env Genes Within the Cow (Bomentioning
confidence: 97%
“…Current hypothesis supports that syncytin-Rum1 was integrated into ruminant genomes 20 MYA while Fematrin-1 was integrated into the bovine genome 11 MYA [94]. As for bERVE-A, its mRNA is found only in binucleate cells throughout the gestation period, and this gene contains syncytin 1-like SU domain and ASCT2 binding domain; however, it does not possess fusogenic activity due to a loss of the fusion peptide [76]. Furthermore, the integration of BERV-P was recently found in ruminants [95].…”
Section: Endogenous Retroviruses and Pregnancymentioning
confidence: 53%
“…Evidence has accumulated that ERVs are now realized as factors implicated in development and differentiation of TE cells in mammalian species such as humans, rodents, dogs/cats, rabbits, sheep, cattle, tenrecs and opossums [70][71][72][73][74][75][76][77][78]. During the course of evolution, all vertebrates have been exposed to multiple waves of cross-species infection by exogenous retroviruses, some of which infected germ cells and have been inherited in an integrated, proviral form [79].…”
Section: Endogenous Retroviruses and Pregnancymentioning
confidence: 99%
“…We recently reported that the BERV‐K1 Env , fematrin‐1 , is conserved in the genome of the Bovinae species and that it is specifically expressed in BNCs of the placenta and exhibits fusogenic activity, using different types of cells, except for trophoblast cells, in vitro (Baba et al ; Koshi et al ; Nakaya et al ). However, there is no direct evidence regarding whether fematrin‐1 possesses fusogenic activity in trophoblast cells.…”
Section: Introductionmentioning
confidence: 99%